Job Attitude and Employee Performance: An Empirical Study of Non-Academic Staff of Bauchi State University Gadau Nigeria - Inuwa, Mohammed; Mashi, Munir Shehu; Salisu, Isyaka Mohammed (International Journal of Business and Management Future, 2017)
Getting the best out of an employee has always been a major challenge an employer face in today’s competitive environment. These might be however, connected to the fact that an employee is most dynamic and unpredictable aspect of business resources. It has therefore become imperative for organisations to realise the significance of an employee and also the device strategic means through which an employee can be influenced in order to develop positive job attitudes that can lead to higher performance. Hence, the study aims to examine the relationship between job attitude and employee performance by using the non-academic staff of Bauchi State University Gadau as unit of analysis. An aggregate of two hundred and seventy questionnaires were distributed non- academic staff of BASUG based on systematic random sampling and data collected was analysed using Statistical Package for Social Sciences (SPSS). The outcome of the analysis shows that there is positive and significant relationship between job attitude and employee performance. Also, the study is limited due to the fact that it adopts only two variables and concentrate in one institution only. Thepaper recommends that employers should prioritise important motivational factors that will bring about positive job attitude so as to achieve highest performance level of an employee. Furthermore, the study will serve as a policy guide to the management of the Nigerian Universities in areas relating to employee performance improvement through job attitude and it will also further make an impetus the field of organisational behaviour and human resource management.